Analysis of the Indonesian Criminal Code's Respect for Animals - Isnawan, Fuadi (Jurnal Hukum Magnum Opus, 2025)
his research delves into the intricate legal framework governing animal protection within the Indonesian Criminal Code, offering a thorough analysis of existing provisions aimed at ensuring animal welfare. Indonesia's commitment to humane treatment and ethical considerations in its legal system is underscored by several articles directly or indirectly addressing the welfare of animals. Employing a normative juridical approach, this study systematically examines the statutory provisions pertaining to animal welfare within the Indonesian Criminal Code. The findings illuminate the Indonesian Criminal Code as a robust legal framework that prioritizes respect, dignity, and compassion for animals. Article 302 serves as the cornerstone by establishing fundamental standards for humane treatment, reflecting intrinsic moral values deeply embedded within Indonesian societal norms. Complementing this, Article 409 addresses actions that incite animal aggression, thereby safeguarding both the physical and psychological well-being of animals. Article 540 further strengthens these protections by ensuring animals are shielded from excessive workloads and inhumane transportation practices, thereby addressing their rights and welfare comprehensively. Moreover, Article 541 specifically focuses on horses, mandating that they are not subjected to overwork and are treated with due consideration for their natural development and capabilities. Additionally, Article 544 regulates contentious activities such as cockfighting, aiming to maintain public order while upholding humane standards and preventing unnecessary suffering among animals. These provisions collectively demonstrate Indonesia's holistic approach to animal welfare, balancing societal needs with ethical imperatives.